(untitled) (Bangladesh Journal of Anatomy, 2017)
Context: The three jaw chuck pinch refers to an act where placing the object between the pad of the distal phalanx of the thumb opposing the pads of the distal phalanges of both the index finger and the middle finger. Pinch strength is generally influenced by the health status and level of physical activity of a person. Objectives: The present study was planned to correlate the three-jaw chuck pinch strength with hand thickness in electronics technicians working in Dhaka Metropolitan City. The data obtained from the study may be used as a base line for other professions as well as for research in our country. Materials & Methods: A cross sectional, analytical study was carried out in the department of Anatomy, Dhaka Medical College, Dhaka during the period of July 2015 to June 2016 on 100 adult male electronics technicians and 100 adult sedentary workers. Electronics technicians were considered as case group and sedentary workers were considered as control group. Case group was further subdivided according to their working experiences. Study subjects were selected by convenient purposive sampling technique. Hand thickness was measured by digital slide calipers and pinch gauge was used to measure the threejaw chuck pinch strength. Results: The mean three-jaw chuck pinch strength was significantly higher (P<0.05) in case group than in the control group. Significant difference was also observed between case group and control group in the mean hand thickness (P<0.05). Mean hand thickness was greater in case group than that of control group. Three-jaw chuck pinch strength showed significant positive correlation with hand thickness in case group. Case group was further subdivided according to their working experiences, the mean threejaw chuck pinch strength and hand thickness was significantly higher (P<0.05) in more working experience group than in less working experience group. Conclusion: Three-jaw chuck pinch strength showed significant positive correlation with hand thickness. Bangladesh Journal of Anatomy July 2017, Vol. 15, No. 1, pp. 29-34